2020
DOI: 10.3390/scipharm88040044
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Loaded Nanoemulsion for Better Cellular Permeation

Abstract: Curcumin nanoemulsion was prepared using coconut oil, Tween 80 (surfactant) and polyethylene glycol (co-solvent) with the addition of honey and glycerol as additives. The nanoemulsion was optimized and systematically characterized for transdermal delivery. Small particle size (15.92 nm), low polydispersity index (0.17) and slight acidic (pH 4.18) curcumin nanoemulsion was obtained without any chemical degradation based on the Fourier transform infrared (FTIR) spectrum. The incorporation of curcumin inside nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Arechabala et al tested various surfactants against normal human fibroblasts, and in their study, Tween 80 appeared to be the least cytotoxic [29]. It is successfully used in other nanoemulsions with no cytotoxic effect-with applications for skin [30,31] and food [32]. The CBD was evaluated by Petrosino et al in the HaCaT cell line-no effect was observed with 1, 5, 10, and 20 µM of CBD after 6, 12, and 24 h [33].…”
Section: Biological Skin Response In Vitro and In Vivomentioning
confidence: 99%
“…Arechabala et al tested various surfactants against normal human fibroblasts, and in their study, Tween 80 appeared to be the least cytotoxic [29]. It is successfully used in other nanoemulsions with no cytotoxic effect-with applications for skin [30,31] and food [32]. The CBD was evaluated by Petrosino et al in the HaCaT cell line-no effect was observed with 1, 5, 10, and 20 µM of CBD after 6, 12, and 24 h [33].…”
Section: Biological Skin Response In Vitro and In Vivomentioning
confidence: 99%
“…Among other actions known so far, CUR effectively promotes wound healing at low doses either free [ 39 ] or incorporated in nanocarriers [ 44 ] as it is involving in the proliferation and migration of fibroblasts that is initiated at the second phase of wound healing. The comparison of the action of CUR free or incorporated in nanocarriers was not reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, the CSN and the physical mixture were ground into powder and pressurized at a pressure of 5 tonnes for 5 min in a KBr press (Technosearch Instrument Mumbai, India) to form pellets or thin films, and FT-IR spectra were recorded in the wavelength range 4000-400 cm -1 for each. 18…”
Section: Fourier Transform Infrared (Ft-ir) Analysismentioning
confidence: 99%